ANALYSIS OF ECONOMETRIC MODELING STEPS (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2024)
This article investigates the main stages of econometric modeling, their unique characteristics in various fields and the economy, as well as the sequence and content of the stages of economic-mathematical modeling